Pendidikan dan Latihan Dasar Perkoperasian Angkatan II Tahun 2023: Urgensi, Implementasi dan Ukuran Capaian Promosi Anggota - Supriyadi, Deddy (E-Coops-Day, 2024)
Member Promotion topic was delivered at the 2023 Cooperative Training and Training Class II. The training participants were State Civil Apparatus (ASN). This material is presented to make participants understand what member promotion is, the importance of member promotion, and implementing and measuring its achievements. The training method is carried out using the andragogy education method and the "3E" principle (Explain, Educate, Entertain). The training was conducted effectively, as reflected in the enthusiasm during the training and the evaluation results. An understanding of member promotion is very basic; therefore it must be understood by cooperative activists. It means member promotion material is one of the most important materials to be conveyed in training on the basics of cooperatives.